Aboveground litter production and bioelement potential return in an evergreen oak (Quercus rotundifolia) woodland near Salamanca (Spain) - Martin, A; Gallardo, J F; Santa Regina, I (Ann. For. Sci., 1996)
Total aboveground production of trees has been determined in a Quercus rotundifolia evergreen oak woodland developed over a chromic Luvisol. The woodland is located close to the city of Salamanca (central-western Spain). Litter fall occurs throughout the year, with a maximum from April to June owing to leaf fall. Mean litter production is 1.9 Mg ha-1 year-1, although variations from year to year are observed, mostly due to water stress in summer. The mean area of influence of litter fall of each tree is about 4 m outside the crown shadow and the leaf percentage (55%) over the total aboveground litter production shows that the system is mature. Tree inflorescences are found to have the highest concentration in bioelements, although the latter are mostly returned through the leaves (with the exception of K).
Keywords: biogeochemical cycles; evergreen oak; litter fall; potential return of bioelements; Quercus rotundifolia Lam